Global education policy and international development new agendas, issues and policies - Verger, Antoni 1975-; Novelli, Mario; Altinyelken, Hülya K. (London ; New York Bloomsbury Academic, An imprint of Bloomsbury Publishing Plc, 2017)
"How are global education agendas and policies formed and implemented? What are the effects of political and economic globalization on educational reform and change? What are the limitations of globalised policy solutions and what problems do they encounter at local levels? What is the impact of such policy priorities as public-private partnerships, child-centred pedagogies and school-based management? Exploring the interplay between globalization, education and international development, this comprehensive introduction surveys the impact of global education policies on local policy in developing countries. With chapters written by leading international scholars in the field, drawing on a full range of theoretical perspectives and offering a diverse selection of case studies, this new edition has been revised and updated throughout to reflect changing policy debates and issues whilst maintaining the theoretical and intellectual coherence of the first edition. This second edition of Global Education Policy and International Development includes: - Seven entirely new chapters on the emerging debates in the field, including large-scale assessments, quality of teaching and education in emergencies - Contributions from the leading scholars in the field, such as Steven Ball, Roger Dale and Gita Steiner-Khamsi - Supportive pedagogical features such as chapter outlines, questions for discussion, key reading recommendations and boxed case studies and vignettes - Updated case studies from a variety of countries in the Global South - Online resources, including additional case studies and links to relevant policy documents and video content From students of education, development and globalization to practitioners working in developing contexts, Global Education Policy and International Development is an essential textbook for those seeking to understand how global forces and local realities meet to shape education policy in the developing world."--Provided by publisher.
"Drawing on international case studies and a range of theoretical perspectives, this new edition explores the latest research and debates on the impact of globalization on local education policy in developing countries"--Provided by publisher.
Machine generated contents note: -- Acknowledgements -- Notes on Contributors -- Part I: Introduction: Theoretical and Methodological Insights -- 1. Global Education Policy and International Development: An Introductory Framework, Antoni Verger (Universitat Autonoma, Spain), Mario Novelli (University of Sussex, UK) and Hülya Kosar Altinyelken (University of Amsterdam, The Netherlands) -- 2. Researching Global Education Policy: Angles In/On/Out... Susan L. Robertson (University of Bristol, UK) -- 3. New Forms of Governance in Education Policy Making: Spaces of 'meetingness' in Policy Networks from England and Brazil, Stephen J. Ball, Marina Avelar and Dimitra Pavlina Nikita (UCL Institute of Education, UK) -- Part II: Global Education Policy: Case Studies -- 4. Silences, Stereotypes and Local Selection: Negotiating Policy and Practice to Implement the MDGs and EFA, Elaine Unterhalter (UCL Institute of Education, UK) -- 5. International Large-Scale Assessments in Lower and Middle Income Countries: Rationales for Participation and Changing Policy Processes, Camilla Addey (Humboldt University, Germany) and Sam Sellar (University of Queensland, Australia) -- 6. School- and Community-based Management as Global Education Policy: History, Trajectory, Geography, D. Brent Edwards Jr. (Drexler University, USA) -- 7. Conditional Cash Transfers in Education for Development: Emergence, Policy Dilemmas and Diversity of Impacts, Xavier Bonal (Universitat Autonoma, Spain), Aina Tarabini (Universitat Autonoma, Spain) and Xavier Rambla (Universitat Autonoma, Spain) -- 8. Teachers and the 2030 Global Education Agenda: Ensuring Equality and Quality Education, Yusuf Sayed (Cape Peninsula University Technology, South Africa) -- 9. Adopting the Dual Policy Model of Technical and Vocational Education and Training: The case of Mexico, Oscar Valiente (University of Glasgow, UK) -- 10. A Converging Pedagogy in the Developing World: Insights from Uganda and Turkey, Hülya Kosar Altinyelken (University of Amsterdam, The Netherlands) -- 11. Education in Emergencies in a Globalising World: Emergence of a Field, Mario Novelli (University of Sussex, UK) and Mieke Lopes Cardozo (University of Amsterdam, The Netherlands) -- 12. Privatization 'by Default': Low-Fee Private Schools in Low-Income Countries, Antoni Verger (Universitat Autònoma de Barcelona, Spain) -- Part III: Conclusions -- 13. Measuring and Interpreting Re-Contextualization: A Commentary, Gita Steiner-Khamsi (University of Columbia, USA) -- 14. Global Education Policy: Creating Different Constituencies of Interest and Different Modes of Valorisation, Roger Dale (University of Bristol, UK) -- Bibliography -- Index.
Includes bibliographical references.
Keywords: Education -- Economic aspects -- Developing countries; Education and state -- Developing countries; Education and globalization -- Developing countries; Economic development -- Developing countries